Report of the St. Marys River - Little Rapids Cut Ice Boom and Its Effects on Levels and Flows in the Soo Harbor Area - CORPS OF ENGINEERS DETROIT MI DETROIT DISTRICT (1980)
The St. Marys River is a key link in the Great Lakes-St. Lawrence Seaway transportation system. Prior to the winter of 1975-76, experience had shown that winter ship traffic produced some restriction of normal travel and commerce between Sugar Island and the mainland. These restrictions were caused by broken, floating ice entering Little Rapids Cut from the harbor at Sault Ste. Marie (Soo), Michigan and Ontario causing ice build-up in the Cut. To help alleviate this problem and to act as an aid to winter navigation, an ice boom with a 250-foot-wide navigation opening was installed for the winter of 1975-76 at the outlet of Soo Harbor to stabilize the ice cover in the harbor. This boom has been deployed each winter since. This report documents the field observation program and analyzes the collected data to evaluate the effectiveness and reliability of the ice boom in stabilizing Soo Harbor ice and water levels. Keywords: Water flow; Water levels; Monitoring; Ice thickness.